2012
DOI: 10.1186/1756-3305-5-129
|View full text |Cite
|
Sign up to set email alerts
|

Social economic factors and malaria transmission in Lower Moshi, Northern Tanzania

Abstract: BackgroundFor many years social economic status has been used as an indicator to characterize malaria treatment seeking behaviors of communities and their adherence to malaria control programs. The present study was therefore conducted to assess the influence of household social economic status, knowledge, attitude and practice on treatment seeking behaviors, distance to health facilities and vector control measures in the Lower Moshi area, northern Tanzania.MethodsA cross-sectional household survey was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 63 publications
5
26
0
1
Order By: Relevance
“…Nonetheless, we found a significant relationship between education and malaria but education may indirectly effect on knowledge of malaria among Afghani participants as well as Baluchis. Similarity, a significant association between education level and Knowledge on malaria transmission, prevention, and treatment was reported in some African countries [17][18][19].…”
Section: Discussionsupporting
confidence: 65%
“…Nonetheless, we found a significant relationship between education and malaria but education may indirectly effect on knowledge of malaria among Afghani participants as well as Baluchis. Similarity, a significant association between education level and Knowledge on malaria transmission, prevention, and treatment was reported in some African countries [17][18][19].…”
Section: Discussionsupporting
confidence: 65%
“…In general, children less than 5 years old had the highest frequencies of parasitemia, pointing to agedependent determinants of protection that may or may not be the product of cumulative exposure to infection during life. 80,81 Increasing household distance to a health facility, a known risk factor for malaria, 82,83 was also identified as a significant risk factor for patent parasitemia in bivariate analysis. However, this relationship failed to retain significance in the multivariate model, likely confounded by the distance to larval habitats.…”
Section: Discussionmentioning
confidence: 96%
“…Over accumulation of hepcidin reduces the available iron in circulation hence hard times for parasite's survival. Because 60% of Kampala city habitants live in slums such as Katanga [1] where social amenities are a big problem, families in these areas live in overcrowded conditions and makeshift shelters exposed to open sewers, mosquito breeding grounds [20,21] these make them vulnerable to malaria infections. This study found a relatively high malaria infection rate especially among children in this area as compared to one reported other parts of the city and this could as result of geographic and social disadvantages of the area [1].…”
Section: Discussionmentioning
confidence: 99%